Pengaruh Model Pembelajaran Berbasis Proyek (PjBL) terhadap Kemampuan Pemecahan Masalah Mahasiswa Ilmu Komputer dalam Pengembangan Aplikasi - Palma Juanta; Eddy Tanadi; Patricia Angelin; Theo Parta (Yayasan Literasi Sains Indonesia, 2025)
This study examines how Project-Based Learning (PjBL) model affects Computer Science students’ ability to solve problems during application development. As technology continues to advance, students must primarily focus on problem solving to succeed in the field of computer science. Project-Based Learning (PjBL) allows students to learn the subject through real-world contexts by facing real-life project assignments that involve the process of problem identification and in-depth analysis and design of solutions. This study examines how PjBL affects students’ ability to collaborate and communicate and solve problems and challenges that arise when PjBL is implemented. This study uses a quantitative approach with a quasi-experimental design in which 30 Computer Science students from Prima University were involved. Analysis of the results found that the implementation of PjBL provided significant improvements in students’ problem-solving abilities as well as enhancing the development of their teamwork skills and creativity. The PjBL model has proven its effectiveness in preparing students to overcome various challenges in a complex and dynamic workplace. Higher education should use PjBL more often to improve students’ skills in information technology.